Economic nationalism and international interdependence : the global costs of national choices - Peterson g. peter (Washington D.C: PER Jacobsson foundation, 1984)
This lecture contains some of the highlights of national interdependence of U.S economics in relation to global costs of national choices or assets.
Include bibliography
asm; 12/02/19
Loans
Keywords: Economic history; Economic policy; United State